2022
DOI: 10.3390/children9091286
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Fitness Index and Psychological Symptoms in Chinese Children and Adolescents

Abstract: The aim of this study was to determine the relationship between different physical fitness indices (PFIs) and psychological symptoms and each dimension (emotional symptoms, behavioral symptoms, social adaptation difficulties) of Chinese children and adolescents. Methods: A total of 7199 children and adolescents aged 13–18 in Jiangxi Province, China, were tested for grip strength, standing long jump, sit-ups, sit and reach, repeated straddling, 50 m run, 20 m shuttle run test (20 m SRT) items. The physical fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Speci cally, higher physical tness levels among LBC predicted a lower risk for psychological symptoms, and lower PFI levels may have a negative impact on their psychological health. Our study results supported those of Chen et al [31] and Lu et al [23], which found that adolescents' physical tness was associated with their psychological health status. Some possible explanations have been put forward to explain the underlying mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Speci cally, higher physical tness levels among LBC predicted a lower risk for psychological symptoms, and lower PFI levels may have a negative impact on their psychological health. Our study results supported those of Chen et al [31] and Lu et al [23], which found that adolescents' physical tness was associated with their psychological health status. Some possible explanations have been put forward to explain the underlying mechanism.…”
Section: Discussionsupporting
confidence: 92%